Effects of single nucleotide polymorphisms on the binding of afatinib to EGFR : a potential patient stratification factor revealed by modeling studies - Kannan, Srinivasaraghavan (2020)
The anticancer drug afatinib has been found to be more effective at inhibiting the oncogenic EGFR mutant exon 19 deletion (19del) over the oncogenic EGFR mutant L858R. The underlying mechanism has been hypothesized to result from differences in structural constraints introduced by the mutations and stabilizing interactions afforded by a buried water molecule in 19del (Kannan, S.; et al. Sci. Rep. 2017, 7, 1540). The COSMIC cancer database is mined for EGFR sequences to discover that several mutations in the form of Single nucleotide polymorphisms (SNPs) line this hydration cavity. In this work, the effects of these SNPs on the affinity of afatinib for EGFRWT and oncogenic mutants EGFRL858R and EGFR19del were studied using free energy perturbation and thermodynamic Integration calculations. The simulations reveal that several SNPs have significant effects on the affinity of afatinib for the mutant EGFRs carrying the SNPs and may thus have clinical implications relating to emergence of resistance to afatinib, thus potentially impacting the choice of EGFR inhibitors in the clinic.